The role of subgroup analyses: results from the NOVA trial: - Di Maio, Massimo; Bergamini, Alice (Cancer Breaking News, 2017)
The clinical efficacy of poly-adenosine diphosphate (ADP) ribose polymerase (PARP) inhibitors in BRCA-mutated ovarian cancer patients has been widely reported. However, novel challenges are currently aimed at broadening the benefit of PARP inhibitors to patients with wild-type BRCA and homologous recombination deficiency (HRD) and identifying a test able to select those patients who might benefit most from this therapy. The recently published ENGOT-OV16/NOVA trial reported an advantage in progression-free survival (PFS) for patients receiving the PARP1/2 inhibitor niraparib, as maintenance treatment for platinum-sensitive ovarian cancer compared to placebo, regardless of their germline BRCA or HRD status. This suggests that niraparib could potentially represent a valuable maintenance option for virtually all patients with platinum-sensitive relapsed ovarian cancer and that the HRD assay used in this trial is not able to reliably identify those patients who benefit the most from niraparib maintenance. These provocative considerations are the result of subgroup analyses that should be interpreted with caution but are useful to show the consistency of the effect of niraparib across the whole population.